Family Conflict Reflected In Breaking Night Novel (2010):A Sociological Approach - Kurniawati, Melinda Ayu Diyah, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M. Hum (2014)
The major issue of this study is; How is the family conflict of Liz's family reflected in Breaking Night novel (2010)? The objective of this study is to analyze Liz Murray in Breaking Night novel (2010) based on the structural elements of the novel and to describe the family conflict of Liz's family reflected in Breaking Night novel (2010) based on sociological approach. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. Primary data source of this research is the novel Breaking Night novel (2010) that written by Liz Murray and the secondary data sources are the author's biography, essay, comment, homepage, and website about the novel and other relevant sources. The data analysis method is descriptive qualitative analysis based on sociological approach. The results of the study show; The Major character is the writer her self, Liz Muray and the minor character is Dad (Liz's father) and Ma (Liz's mother), grandma, Rick and Dany and also Lisa (Liz's sister). The next is setting, it consists of setting of time and setting of place. The setting of time is at the beginning of 1977 until 2009. The plot, first is exposition where the story started when Liz looks the old black and white picture of her mother. It's 4x7. The complication where the conflict itself can be divided into internal conflict and external conflict. External conflict happens between Liz and her parent. The climax happens on Liz's life, when she accepts the bad news from her sister Lisa. The resolution of this story is that, on the final of Liz's hard life, she finds out a huge success. The point of view of this novel is Breaking Night is more like an adventure story of Liz Muray rather than a moral story about drug addict. The theme of the novel is 'The strongest power of women to runs from family conflict'. Economical aspect there are several economical aspects that are related with the live of American society in 20th century, where it is about the hard life to live in America and to find a proper work. Political aspect, there are several cases that show about the political aspect related with urban and rural. Cultural aspect where the urban people will do everything to gets their joy.